IMPLEMENTASI MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN PROSES PEMBELAJARAN IPS SISWA KELAS IVA SD NEGERI 146 PEKANBARU - Dalhayayani '; Mahmud Alpusari Alpusari; Otang Kurniaman Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to improve the learning process and achievement of school year 2014/2015. The subjects of the research was the students class IVA of SDN 146 Pekanbaru in number 37 students. It is a classroom research by two cycles. The data of the research shows that the learning proces and achiement having improved. It is proven by the score result of the theacher’s activity on the cycle I by mean 60% (enough category) improved as 10% to 70% (good category) and cycle II 80% (good category) improved as 5 % to 85% (very good category). The students activity on the cycle I by mean 60% (enough category) improved as 5% to 65% (good category) and the cycle II improved by mean 75% (good category) improved as 10% to 85% (very good category). The research finding also having improved, where before the problem based learning model. Was implemented on the passed based score was 16 students (43,24%) by mean 62,75. The cycle I, the passed students having improved as 23 students (62,16%) by mean 73,83 and on the cycle II improved to be 31 students (83,78%) by mean 80,54. By the improvement of the achievement overall is 28,35%. Therefors it can be concluded that the hypothisis of this reseach are (1) If the problem based learning is implemented, so the sosial learning process of the students class IVA SDN 146 Pekanbaru is improved (2) If the problem based learning is implemented, so the sosial learning achievement of the students class IVA SDN 146 Pekanbaru is improved. Keywords. Problem based learning model. Learning process and achievement